“Aplicación web como estrategia informática para la gestión de los perfiles de titulación de la Facultad De Ciencias Administrativas De La Universidad Técnica De Cotopaxi.” - López Villacis, Darío Fernando (2021)
The following technological proposal had as a plan the design of a web application which allowed to improve the management and control of the degree process in the Faculty of Administrative Sciences of the Technical University of Cotopaxi where a problem was found in the existing processes, for this For this reason, the objective of developing a web application was established, through a methodology and programming tools that allowed managing the processes that entail a degree, in this way the work of the administrative staff was considered in the repetitive activities that are carried out during the management of each process . For this, a RUP research methodology was applied using a framework in such a way that the project is coupled to said methodology, which has an adequate structure for the application development process, taking into account the realization of UML modeling. Tools were established that allowed the design and construction of the software